2020
DOI: 10.1044/2020_jslhr-19-00395
|View full text |Cite
|
Sign up to set email alerts
|

Disfluency Characteristics of 4- and 5-Year-Old Children Who Stutter and Their Relationship to Stuttering Persistence and Recovery

Abstract: Purpose The purpose of this study is to document disfluency behaviors expressed by 4- and 5-year-old children who stutter and to identify whether stuttering characteristics at this age are predictive of later stuttering recovery or persistence. Method We analyzed spontaneous speech samples from 47 children diagnosed with developmental stuttering when they were 4–5 years old. Based on their eventual diagnosis made the final year of partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 28 publications
2
10
1
Order By: Relevance
“…Yairi and Ambrose (1999) confirmed that the frequency of typical disfluencies did not differentiate groups of CWS and children who do not stutter (CWNS). We and others also note that the frequency of typical disfluencies is statistically similar between groups of CWS-ePer and CWS-eRec (Singer et al, 2020;Walsh et al, 2020). On the other hand, stuttering-like disfluencies (SLDs)-sound prolongations, blocks, sound/syllable repetitions, and monosyllabic whole-word repetitions-not only differentiate CWS from those who do not stutter but also distinguish CWS-ePer and CWS-eRec (Walsh et al, 2020).…”
Section: Severity Of Stuttering-like Disfluenciessupporting
confidence: 61%
See 4 more Smart Citations
“…Yairi and Ambrose (1999) confirmed that the frequency of typical disfluencies did not differentiate groups of CWS and children who do not stutter (CWNS). We and others also note that the frequency of typical disfluencies is statistically similar between groups of CWS-ePer and CWS-eRec (Singer et al, 2020;Walsh et al, 2020). On the other hand, stuttering-like disfluencies (SLDs)-sound prolongations, blocks, sound/syllable repetitions, and monosyllabic whole-word repetitions-not only differentiate CWS from those who do not stutter but also distinguish CWS-ePer and CWS-eRec (Walsh et al, 2020).…”
Section: Severity Of Stuttering-like Disfluenciessupporting
confidence: 61%
“…Our longitudinal data also indicated that CWS-ePer (n = 18; M = 36.3 months) began stuttering approximately 2 months later than the group of CWS-eRec (n = 29; M = 34.3 months). This difference was also not statistically significant; the two groups largely overlapped (Walsh et al, 2020). The recent meta-analysis by Singer et al (2020) reported later ages at stuttering onset for children who would eventually persist.…”
Section: Epidemiological Factorsmentioning
confidence: 82%
See 3 more Smart Citations